Nanomaterials for Solid State Hydrogen Storage - Varin, R. A. (Springer, 2017)
Over the past decade, important advances have been made in the development of nanostructured materials for solid state hydrogen storage. The stored hydrogen will be used in fuel cells for generation of electricity in a clean, inexpensive, safe and efficient manner. Nanomaterials for Solid State Hydrogen Storage focuses on nanomaterials having high volumetric and gravimetric hydrogen storage capacities, and thus having the highest potential of being applied in the automotive sector. Written by leading experts in the field, Nanomaterials for Solid State Hydrogen Storage provides a thorough history of hydrides and nanomaterials, followed by a discussion of existing fabrication methods. The authors' own research results on the behavior of various hydrogen storage materials are also presented. Covering fundamentals, extensive research results and recent advances in nanomaterials for solid state hydrogen storage, this book serves as a comprehensive reference.